FUNSTATION (FUN STATISTICS EDUCATION) SEBAGAI ALTERNATIF UNTUK MENINGKATKAN PEMAHAMAN STATISTIKA SISWA SEKOLAH MENENGAH PERTAMA - Fadlilah, ChusnuL; Meilina, Dika Dwi; Hasanah, Ika Nur; Kohar, Ahmad Wachidul (Galois: Jurnal Penelitian Pendidikan Matematika, 2022)
In the era of the industrial revolution 4.0 and society 5.0, the world's development became very fast and unlimited. Therefore, to face these challenges, it is necessary to have quality human resources who are competent, ready to compete and compete. Quality human resources can be developed through both formal and non-formal education. The better quality of education will encourage the realization of a comprehensive understanding of students so as to form a young generation that is intelligent, critical, creative, innovative and accomplished. The development of quality human resources is needed at all levels of education, one of which is the junior high school level. However, junior high school students still have difficulty in learning statistics. To overcome these difficulties, an innovative product was developed in the form of statistical learning media FUNSTATION (Fun Statistics Education). Development research was conducted to develop FUNSTATION (Fun Statistics Education) statistical learning media based on the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The results showed that the assessment met the criteria of validity, practicality and effectiveness. Validity is fulfilled based on an assessment by a media expert lecturer. Meanwhile, practicality and effectiveness were obtained based on the results of questionnaires on junior high school students. The results of the questionnaire and trial test showed that the use of FUNSTATION (Fun Statistics Education) from 10 students stated that it was practical and effective. So it can be concluded that the learning media FUNSTATION (Fun Statistics Education) has met the three assessments that can improve statistical understanding. ABSTRAK Pada era revolusi industry 4.0 dan society 5.0 perkembangan dunia menjadi sangat cepat dan tak terbatas. Oleh karena itu untuk menghadapi tantangan tersebut diperlukan kualitas sumber daya manusia yang memiliki kompetensi, siap bersaing dan berkompetisi. Sumber daya manusia yang berkualitas dapat dikembangkan melalui pendidikan baik formal maupun nonformal. Kualitas pendidikan yang semakin baik akan mendorong terwujudnya pemahaman siswa secara komprehensif sehingga terbentuk generasi muda yang cerdas, kritis, kreatif, inovatif dan berprestasi. Pengembangan kualitas sumber daya manusia yang berkualitas diperlukan dalam semua jenjang pendidikan salah satunya jenjang sekolah menengah pertama. Namun, siswa sekolah menengah pertama masih mengalami kesulitan pada materi pembelajaran statistika. Untuk mengatasi kesulitan tersebut dikembangkan produk inovatif berupa media pembelajaran statistika FUNSTATION (Fun Statistics Education). Penelitian pengembangan dilakukan untuk mengembangkan media pembelajaran statistika FUNSTATION (Fun Statistics Education) berdasarkan model ADDIE (Analyze, Design, Develop, Implement, Evaluate). Hasil penelitian menunjukkan bahwa penilaian memenuhi kriteria kevalidan, kepraktisan dan keefektifan. Kevalidan dipenuhi berdasarkan penilaian oleh dosen ahli media. Sementara kepraktisan dan keefektifan diperoleh berdasarkan hasil kuesioner pada siswa SMP. Hasil kuesioner dan tes uji coba menunjukkan bahwa penggunaan FUNSTATION (Fun Statistics Education) dari 10 siswa menyatakan praktis dan efektif. Sehingga diperoleh kesimpulan bahwa media pembelajaran FUNSTATION (Fun Statistics Education) telah memenuhi ketiga penilaian yang dapat meningkatkan pemahaman statistika.